Frugal innovation in wound care: a critical discussion of what we can learn from low-resource settings. (10th November 2022) - Stephens, Melanie; Wynn, Matthew; Pradeep, Sheba; Bowshall, Janine
Abstract : Frugal innovation is a common philosophy in low-income settings due to limited access to resources. However, with both the increasing prevalence and clinical acuity of patients with wounds in the UK, it is essential that alongside innovation such as harnessing cutting-edge new technologies, frugal innovation is also pursued. This may improve both economic efficiency and patient outcomes. Frugal innovations were adopted throughout the COVID-19 pandemic and included opportunistic solutions such as video-conferencing services to run clinics. However, there are many more opportunities for frugal innovation in wound care, including the use of smartphone technology, which is already accessible to 99.5% of UK clinicians caring for wounds, or the simplification of wound-assessment processes using pulse oximeters as an alternative to dopplers, as in the Lanarkshire Oximetry Index. This article explores what frugal innovation is and how it could improve UK wound services. The authors invite clinicians working in wound care to consider their access to existing resources that may not be considered useful for wound-care processes and explore how these could be used to improve clinical outcomes.